Montichneumon, a new genus of Ichneumoninae (Hymenoptera, Ichneumonidae) from the high mountains of Taiwan - Hsuan-Pu Chen; Namiki Kikuchi; Shiuh-Feng Shiao (European Journal of Taxonomy, 2025)
A new genus and species, Montichneumon Chen & Kikuchi gen. nov. and Montichneumon immortalibestia Chen & Kikuchi gen. et sp. nov., are described from the high mountains of Taiwan. This new genus is identified as belonging to the Amblyteles genus-group (previously known as subtribe Amblytelina, tribe Ichneumonini). The status of the new genus is confirmed based on morphological comparison and a multigene phylogeny using concatenated 28S and COI sequences. Montichneumon can be distinguished from other related genera by its enlarged second segment of maxillary palps, smooth and sparsely punctate postpetiole, weakly convex scutellum without lateral carina, and narrow, elongate gastrocoelus. The new genus is compared with morphologically similar genera Achaius Cameron, 1903, Achaiusoides Tereshkin, 2011, Diphyus Kriechbaumer, 1890, Hepiopelmus Wesmeal, 1845, Limerodops Heinrich, 1949, Serratichneumon Riedel & Sheng, 2023, and Tricholabus Thomson, 1894. A diagnostic key to these morphologically similar genera of the Amblyteles genus-group is provided, and the generic position of this new genus is also discussed.